Australian nursing students' perception, knowledge, and attitude towards oral healthcare of older people and associated factors: a national cross-sectional survey - Vandana Bhagat; Ha Hoang; Leonard A. Crocombe; Lynette R. Goldberg (BMC, 2023)
Abstract Background The oral health of many older Australians is poor and associated with many systemic health problems. However, nurses often have a limited understanding of the importance of oral healthcare for older people. This study aimed to investigate Australian nursing students' perception, knowledge, and attitude toward providing oral healthcare for older people and associated factors. Methods A cross-sectional study was conducted among final year nursing students studying at accredited nursing programs using an online self-reported 49-item survey. The data were analysed using univariate and bivariate analysis (t-test, ANOVA, Spearman's correlation test). Results A total of 416 final-year nursing students from 16 accredited programs in Australia completed the survey. Mean scores showed that more than half of the participants felt they lacked confidence (55%, n = 229) and had limited knowledge about oral healthcare for older people (73%, n = 304); however, their attitude towards providing such care was favourable (89%, n = 369). A positive correlation was found between students' confidence in delivering oral healthcare to older people and their perceived knowledge (r = 0.13, p < 0.01). Results revealed a statistically significant positive association between students' experience in providing oral healthcare to older people and students' perception (t = 4.52, p < 0.001), knowledge (t = 2.87, p < 0.01), and attitude (t = 2.65, p < 0.01) mean scores in such care. Nearly 60% (n = 242) of participants received education/training in oral healthcare for older people at university, but this was often for less than one hour. Around 56% (n = 233) believed that the current nursing curriculum did not prepare them to provide effective oral healthcare to older people. Conclusion Findings suggested a need for nursing curricula to be revised to include oral health education and clinical experience. Knowledge of evidence-based oral healthcare by nursing students may improve the quality of oral healthcare for older people.